Systematic Literature Review (Slr): Implementasi Pajak Karbon Di Indonesia Berdasarkan Uu Hpp Dalam Perspektif Ekonomi Kelembagaan - Naila Septa Ridhoni; Taryono Taryono; Melani Noviantori Ramadhan; Wellyn Cesharina Meylan; Syakirah Athiyyah Fitri (CV. SINAR HOWUHOWU, 2026)
The high level of greenhouse gas emissions resulting from industrial activities and fossil energy consumption in Indonesia has prompted the government to establish a carbon tax policy through the Law on Harmonization of Tax Regulations (UU HPP) Number 7 of 2021. This study aims to analyze the implementation of the carbon tax in Indonesia based on the UU HPP from an institutional economics perspective. The method used is a Systematic Literature Review (SLR) of 15 scientific articles published between 2021 and 2026, collected via Google Scholar using a qualitative narrative synthesis technique. The results indicate that although Indonesia has a legal framework aligned with international standards, the implementation of the carbon tax still faces various institutional challenges. These include weak derivative regulations, sub-optimal emission monitoring systems, a lack of inter-agency coordination, as well as resistance from the industrial sector and the public. Institutional strengthening, digitalization of tax administration, and transparency in the utilization of carbon tax revenues are key factors in enhancing policy effectiveness toward sustainable low-carbon development.